Four basic models of GM(1, 1) and their suitable sequences. Issue 2 (3rd August 2015) - Liu, Sifeng; Zeng, Bo; Liu, Jiefang; Xie, Naiming; Yang, Yingjie
Abstract : Purpose: – The purpose of this paper is to provide a foundational reference and practical guidance for modelling small and poor data with incomplete information. Design/methodology/approach: – The definitions of four basic models of GM(1, 1), such as Even Grey Model (EGM), Original Difference Grey Model (ODGM), Even Difference Grey Model (EDGM) and Discrete Grey Model (DGM), are put forward. The properties and characteristics of different models are studied and their equivalence are proved. The suitable sequences of different models are studied by simulation and analysis with homogeneous exponential sequences, nonhomogeneous exponential increasing sequences and vibration sequences. Findings: – The main conclusions have been obtained as follows: first, the three discrete models of ODGM, EDGM and DGM are suitable for homogeneous exponential sequences or sequences which close to a homogeneous exponential sequence; and second the EGM are suitable for nonhomogeneous exponential increasing sequences and vibration sequences. Practical implications: – The outcome obtained in this paper can be consulted for model selection in the course of practical modelling. Originality/value: – This paper systematically defined the four basic forms of model GM(1, 1) and studied their properties and characteristics, especially their suitable sequences. Although significant progress has been made in this field, such a systematic study on these models and their suitable sequences is still missing as far as we know. It can provide reference and basis for people to choose the correct model in the actual modelling process.